Loneliness and Health Outcomes Among Malaysian Older Adults - Hussein, Siti Zuhaida; Ismail, Azera Hasra; Abu Bakar, Suraya Hanim (UI Scholars Hub, 2021)
Background: Loneliness is a major social problem among the elderly all over the world. Methods: A community-based survey was conducted among 380 community-dwelling older adults residing in Malaysia. A proportional stratified random sampling method was used to examine the relationship between health factors and loneliness. Data were collected using the short-form Social and Emotional Loneliness Scale for Adults, Geriatric Depression Scale-15, and RAND SF-20. p < 0.05 was considered to be statistically significant, and data analysis was performed using Statistical Package for the Social Sciences Statistics 26.0 for Windows. Results: Results revealed that 32.6% of the respondents had social loneliness, 39.9% had emotional loneliness, and 9.2% had family loneliness. Bivariate analyses showed that social and emotional loneliness are significantly related to depression. Moreover, emotional and social loneliness were significantly associated with chronic illness. The results of the multiple logistic regression indicated that depression was a significant predictor of social loneliness (OR = 2.5, 95% CI: 1.1–5.7; p = 0.03) and that chronic illness (OR = 0.4, 95% CI: 0.2–0.8; p = 0.02) remained a significant predictor of family loneliness. Conclusions: The loneliness prevalence experienced by older adults is at a low level. The classification of loneliness in this study would be beneficial in the establishment of loneliness intervention strategies.